Analysis of Fresh Tuna Exports From Pelabuhan Perikanan Samudera (PPS) Bungus Padang City, West Sumatera Period 2022-2023 - Ermi Husni; Siti Aisyah; M Amri (Berkala Perikanan Terubuk, 2023)
The research aims to analyze the effect of the price of tuna on the export quantity of fresh tuna from Pelabuhan Perikanan Bungus (PPS Bungus), Padang City, West Sumatra, to analyze the effect of the price of shrimp on the export quantity of fresh tuna from Pelabuhan Perikanan Bungus (PPS Bungus), Padang City, West Sumatra, to analyze the effect of exchange rate on the export quantity of fresh tuna from Pelabuhan Perikanan Bungus (PPS Bungus), Padang City, West Sumatra and to  analyze the effect of the Japan’s GDP Per Capita on the export quantity of fresh tuna from Pelabuhan Perikanan Bungus (PPS Bungus), Padang City, West Sumatra. This research is based on secondary data; namely data on Tuna Prices, Shrimp Prices, Exchange Rates, and Japan's GDP Per Capita This research uses the Error Correction Model (ECM). The results of this research is the price of tuna has a positive effect on the quantity of tuna exports, the price of shrimp has a positive effect on the quantity of tuna exports, the exchange rate has a positive effect on the quantity of tuna exports, and Japan's GDP per capita has no effect on the quantity of tuna exports.